Understanding the Effect of Bioactive Compounds from Spirogyra sp. in Reducing the Protoscolices Viability In-vitro compared with Albendazole Drug - Hadi M. Almayali; Haider M. Alkaabi (Innovations in Biological Science Vol. 6, 2024)
Hydatid cyst disease (HCD) or cystic echinococcosis (CE) is a serious and important zoonotic disease. In the seventh decade of the 20th century, researchers aimed to use benzemidazole and its derivatives such as albendazole (ABZ), mebendazole (MBZ), fenbendazole , and other drugs as a treatment for hydatid cysts disease but 30% Aqueous has completely treated Andasul Alps, while 40-50% have responded after a short period of treatment then the effects of this treatment appeared in the body, especially when used for a long time. This study aims to analyse the Effect of Bioactive Compounds Extracted from Green Algae Spirogyra sp. in Reducing the Protoscolices’ Viability In vitro Compared with Albendazole Drug. The crude alcoholic extract of Spirugera sp. algae with concentrations (250, 500, and 1000) mg/ml and albendazole with concentrations (250, 500, 1000) mg/ml effects was studied in the viability of protoscolices in vitro, the viability of the protoscolices in 10 microliters and the three replicates calculated in the fixed-size method. There were no significant differences in the first three treatments (0,24,48 hours), whereas the coefficients of 72-144 hours showed significant differences. The mean S.D. ± viability of the protoscolices at the highest rate at treatment at 0 hours (33 ± 5.29) protoscolices, while the mean of the protoscolices dropped to the lowest ratio at 144 to 14 ± 1 protoscolices. While the mean S.D.± mean of the protoscolices viability of the treatments 24-120 hours between 31.33 ± 1.52-16.66 ± 1.52 protoscolices. The total number of protosclices ranged from 177-193. The average number of live protoscolices ranged between 170-177 protoscolices/100 µl, While the number of dead protoscolices ranged from 6-16 protoscolices/100 µl. Sixty-nine chemical compounds were extracted from the crude alcoholic extract of Spirogyra sp. Varied between phenols, turbines, fatty acids, hydrocarbons, and heterocyclic compounds. The results of this study showed a decrease in the percentage of the viability of the protoscolices when exposed to the concentrations of the crude alcoholic extract of Spirugera sp. The concentration of 250 mg/ml resulted in a decrease in the percentage of protoscolices from 92.75±0.62 at 0 hours to 27.06±0.48 at 144 hours compared with the control group (76.56 ± 0.79), while the concentration of 500 mg/ml decreased from 92.59±0.58 per hour to 0.14±0.25% at 144 hours compared with the control group, while the concentration was 1000 mg /ml has led to the killing of all protoscolices at 144 hour compared with the control group, The results of used albendazole drug showed significant differences. concentrations reduced the percentage of viability of protoscolices. When exposed to 250 mg/ ml, the result was a decrease from 93.75 ± 0.77 at 0 hour to 4.15 ± 0.36 at 144 hours, while the concentration of 500 mg/ml reduced the percentage from 48 ± 0.85 at 0 hour to 0,4±0.48 at 144 hours, while The concentration of 1000 mg/ml resulted in the killing of all protoscolices indications at 120 hours compared to 0 hour where the percentage of viability of protoscolices was 45.5 ± 0.98. The results of this study showed a similar effect of a Spirogyra sp extract and an albendazole drug on the viability of the protoscolices with increased concentration and duration of exposure to the drug or alcoholic extract.